Comparison of Advanced Children According to West Law, Compilation of Islamic Law, and Traditional Law of Bugis Customs - Anriani Anriani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The objectives of this study are as follows: 1) To determine the comparison to what extent the position of adopted children in inheriting the assets of their adoptive parents according to Western law, compilation of Islamic law and customary law of the Bugis tribe in Wolo District, Kolaka Regency. 2) To find out what are the obstacles in the application of inheritance distribution according to Western Law, Compilation of Islamic Law and Customary Law of the Bugis Tribe in Wolo District, Kolaka Regency. Based on the data analysis, it can be concluded that: 1) Comparing the extent to which the position of adopted children in inheriting the assets of their adoptive parents according to Western law, the Compilation of Islamic Law and Customary Law of the Bugis Tribe in Wolo District, Kolaka Regency is as follows: In Islamic law, adoption does not have legal consequences in terms of blood relations, guardian-guardianship and inheritance relationships with adoptive parents. He remains the heir of his biological parents and the child continues to use the name of his biological father.Meanwhile, according to the West Inheritance Law are: In Staatblaad 1917 No. 129, the legal consequence of adoption is that the child legally acquires the name of the adoptive father, becomes the child born from the marriage of the adoptive parents and becomes the heir of the adoptive parents. That is, as a result of the appointment, all civil relations are cut off, which originates from the offspring due to birth, namely between the biological parents and the child.Meanwhile, according to the Customary Law of the Bugis tribe, they are as follows: When using customary institutions, the determination of inheritance for adopted children depends on the applicable customary law. Especially the Bugis tribal law thatIf the adopted child is obtained from his/her own family environment, it will result in an unbroken relationship between the child and the biological parents in family relations and assets. And if the adopted child is adopted from the environment outside the family, it can result in the relationship between the adopted child and the biological parents being cut off, especially in relation to assets or inheritance. 2) What are the obstacles in the application of inheritance distribution according to Western Law, Compilation of Islamic Law and Customary Law of the Bugis Tribe in Wolo District, Kolaka Regency, namely: because of the lack of legal education for the community in the process of legalizing adopted children, Lack of public understanding and awareness in the process of distributing inheritance.